Enhancing Pre-Transplant Flow Cytometry with Pronase: Applications and Insights - Rizwan, Haniah (Pakistan Journal of Kidney Diseases, 2025)
Pre-transplant Flow cytometry cross-matching (FCXM) is a widely used technique for evaluating organ transplant compatibility. It is crucial for determining the risk of graft rejection and tracking immune responses. Flow cytometry is optimized to identify donor-specific antibodies (DSA) directed toward the human leukocyte antigens (HLA) present in the donor’s cells. Many of these antibodies can mount an immune response to the transplanted organ causing early allograft rejection. However, one of the main disadvantages of FCXM is the limited accessibility of human leukocyte antigen (HLA) epitopes on donor cell surfaces, which makes it difficult to identify DSAs with low affinity. This can lead to a saturation of all available binding sites when they encounter a mismatched donor, especially among sensitized patients who previously had varying degrees of exposure to foreign HLA antigens from transplants, blood transfusions, or pregnancies. Recent research has demonstrated that pronase, a proteolytic enzyme can dramatically boost FCXM sensitivity by cleaving extracellular proteins on the donor cell surface and revealing buried HLA epitopes. This enhancement enables the detection of DSAs that would otherwise be missed by traditional approaches, resulting in a more accurate assessment of transplant compatibility and better prediction of AMR risk. This review looks into the processes by which pronase improves FCXM sensitivity, its therapeutic applications in organ donation, and its potential benefits in treating sensitized patients. It also covers the problems, limitations, and future directions of pronase-enhanced FCXM, providing insight into its role in transplant immunology and personalized medicine.